Role of impression surface cytology in ocular surface disorders - Suruchi Gupta (International Journal of Medical Research and Review, 2015)
Ocular surface impression cytology is useful, least invasive tool in the diagnosis of various ocular surface disorders like dry eye, xerophthalmia, ocular surface neoplasia etc. Its role in diagnosis of ocular surface squamous neoplasia (OSSN) is well established. This technique has also been shown to have good correlation with histopathological diagnosis. Conjunctival impression cytology involves the removal of superficial epithelial cells of the conjunctiva and their study to make out changes in the conjunctival epithelial cells. These changes can be studied with light microscopy, electron microscopy or using the immunological markers. This article is a retrospective review of English literature articles published on ocular surface impression cytology and its application in various disorders. To achieve this purpose, a detailed online Med line search was done for related publications. The relevant articles were studied and required information was obtained.